Community Education for Combating Corruption in Indonesia: Advocacy Studies and Early Character Development - Fadri, Zainal (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2023)
Corruption is a problem faced by almost all countries. This study aims to further review efforts to eradicate corruption in Indonesia with a character education approach. Character education for the community is a fresh idea for solving corruption problems in Indonesia. This study aims to provide an overview of the prevention or eradication of corruption with other approaches. The approach used is more towards a personal human approach to corrupt behavior. After getting a good understanding of corruption, then a system will be created that will lead every corrupt behavior to self-awareness so that it does not act corruptly. The research data were obtained from literacy collection and then compiled and analyzed in order to obtain an overview and conclusion that corruption cases can be overcome by other methods, namely using the method introduced by Mahatma Gandhi, namely the meaning approach and the human personal approach.